THE EFFECT OF CLASSICAL MUSIC THERAPY ON PAIN INTENSITY IN THE ACTIVE PHASE OF FIRST STAGE OF LABOR AT HARMONI GAJAYANA HOSPITAL MALANG: PENGARUH MUSIK KLASIK SEBAGAI TERAPI TERHADAP INTENSITAS NYERI PADA PERSALINAN KALA I FASE AKTIF DI RSAB HARMONI GAJAYANA MALANG - khumairoh, rizzatul; Hariyanti, Tanti (Journal of Nursing Care and Biomolecular, 2025)
Labor pain is a subjective experience of physical sensations. Various efforts are made to reduce labor pain, one of which is distraction techniques. The purpose of this study was to determine the effect of symphonic music therapy on the intensity of labor pain in mothers in the first active phase of labor. The method used was a pre-experiment with One-Group Pretest-Posttest Design. The population of 41 respondents and the sample of 22 respondents were observed using the Bourbannais pain scale measuring instrument before and after being given music therapy and after being given symphonic music therapy with a purposive sampling technique. To see the effect of symphonic music therapy on the intensity of pain in the first active phase of labor, the Wilcoxon sign rank test was used with the help of a computer. The results of the study were obtained before music therapy, the pain intensity was mostly 77.3% severe pain and 22.7% moderate pain. After music therapy, the intensity of moderate pain was 90.9% and 9.1% experienced severe pain. Based on the results of the analysis, the p value was obtained = 0.000 <α 0.05. Thus, Ho is rejected, meaning that there is an effect of symphonic music therapy on the intensity of labor pain in the first active phase. From these results, symphonic music therapy can be an alternative as labor pain management, which can provide comfort to mothers undergoing the labor process.